HUBUNGAN ANTARA BERPIKIR POSITIF, STRATEGI COPING DAN DUKUNGAN SOSIAL DENGAN KEBERMAKNAAN HIDUP PADA SURVIVOR LETUSAN GUNUNG MERAPI DI YOGYAKARTA - , Frida Corry Octarina, S.psi ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research aims to know the relationship between positive thinking, coping strategies and social support to the meaningfulness of life on Mount Merapi's eruption survivor in Yogyakarta. The subject of this research as many as 64 people who became the Mount Merapi eruption survivor in Yogyakarta. Data collection is done using the scale of positive thinking, coping strategies, scale the scale of social support and the scale of the meaningfulness of life. The results of data analysis with multiple regression showed that positive thinking, coping strategies and social support are jointly acted against the meaningfulness of life on Mount Merapi's eruption survivor with a value of F = level of significance of 27,356 0.001 (p < 0.01). Coefficient of regression of positive thinking, coping strategies and social support of (R) = 0,760 and the effective contribution of average% (R square = 0,578). Furthermore the study also found that social support influential to the meaningfulness of life on Mount Merapi eruption survivor with contribution up to 36.7%, further positive thinking was influential to the meaningfulness of life on Mount Merapi eruption survivor with a contribution of 12.9% and coping strategies of meaningfulness of life on Mount Merapi eruption survivor with contribution up to 8.2%.